Reirradiation for Locally Recurrent Rectal Cancer: A Review - Buchberger, David S.; Miller, Jacob A. (Digestive Disease Interventions, 2025)
Among patients diagnosed with locoregionally advanced rectal cancer requiring neoadjuvant therapy and proctectomy, approximately 5 to 10% will develop pelvic recurrences which are associated with significant morbidity and mortality. After standard neoadjuvant chemoradiotherapy and proctectomy, pelvic recurrences are typically unresectable or borderline-resectable, necessitating consideration of reirradiation using conformal external beam techniques and/or intraoperative radiotherapy to achieve margin-negative resection. Given the heterogeneity of pelvic recurrences in combination with altered pelvic anatomy and adjacent radiosensitive organs, there remains significant uncertainty regarding optimal patient selection, reirradiation techniques, organ tolerances with cumulative radiotherapy doses, and the use of intraoperative radiotherapy. In this article, we review the available evidence supporting the efficacy, toxicity, and techniques of reirradiation with photons, particle therapy, intraoperative radiotherapy, and stereotactic body radiotherapy (SBRT). We highlight the consistent prognostic relevance of surgical resection, techniques to limit toxicity with reirradiation, and contemporary uncertainties regarding the roles of sequential multiagent chemotherapy, particle therapy, SBRT, and intraoperative radiotherapy boost.
Keywords: locally recurrent rectal cancer; reirradiation; hyperfractionation